Intercultural communication for everyday life - Baldwin, John R. 1960- (Hoboken John Wiley & Sons Inc., 2014)
Written for students studying intercultural communication for the first time, this textbook gives a thorough introduction to inter- and cross-cultural concepts with a focus on practical application and social action. The book brings together a group of authors from diverse backgrounds (rhetoric, media studies, organizational approaches, and interpersonal communication) to present a broad view of "communication" that incorporates scientific, humanistic, and critical. theories
Pt. 1. Foundations -- A rationale for studying intercultural communication -- Action, ethics, and research -- Origins -- Pt. 2. Elements -- Subjective culture -- Identity : Struggle, resistance, and solidarity -- Intolerance - acceptance - appreciation -- Pt. 3. Messages -- Verbal communication -- Nonverbal communication -- Rhetoric and culture -- Culture, communication, and media -- Pt. 4. Contexts -- Global media, global cultures -- Adaptation and intercultural competence -- Relationships and conflict -- The political context -- Intercultural communication in international organizational contexts.
Includes bibliographical references and index.
Keywords: Communication -- Philosophy; Intercultural communication